Helminth Fauna in Captive European Gray Wolves (Canis lupus lupus) in Germany - Bindke, Johanna Daniela; Springer, Andrea; Böer, Michael; Strube, Christina (Frontiers in Veterinary Science, 2017)
Captive as well as free-ranging wolves which are currently recolonizing Germany, may harbor a variety of gastrointestinal parasites. This study investigated endoparasites in captive European grey wolves (Canis lupus lupus) using coproscopical methods. Fecal samples were collected monthly between October 2012 and November 2013 from 18 wolf enclosures in 14 German zoological gardens, representing 72 individual wolves. In total, 1,041 fecal samples including 26 bulk samples were analyzed by the sedimentation and flotation method. The most frequently detected egg morphotypes included five nematodes [Ancylostomatidae (Ancylostoma or Uncinaria spp.), Toxocara canis, Toxascaris leonina, Trichuris vulpis and Capillaria/Eucoleus spp.], one cestode (Taeniidae) and one trematode (Alaria alata). 44.76% of all samples were positive for at least one of these egg morphotypes. Overall, Ancylostomatidae showed the highest frequency (30.84% of all samples), followed by Capillaria/Eucoleus spp. (19.88%), Toxocara canis (5.19%), taeniids (3.75%), Trichuris vulpis and Alaria alata (3.65% each) and Toxascaris leonina (1.25%). As fecal samples were collected from the environment and could not be assigned to individual wolves, sample results were combined per zoo and month. General linear mixed models were employed to analyze the effect of season and management factors on the occurrence of Ancylostomatidae, Capillaria/Eucoleus spp., Toxocara canis and taeniids. No statistically significant effect of season was found, whereas anthelmintic treatment negatively affected Ancylostomatidae egg excretion. Detected parasites and their prevalences are comparable to previous studies on wolf parasitism conducted elsewhere in Europe. As many of the most prevalent helminths are of zoonotic importance, routine anthelmintic treatment of captive wolves should be recommended.